SAE Technical Paper Series 2011
DOI: 10.4271/2011-01-0664
|View full text |Cite
|
Sign up to set email alerts
|

A New Combustion System Achieving High Drive Cycle Fuel Economy Improvements in a Modern Vehicle Powertrain

Abstract: Turbulent Jet Ignition is an advanced spark initiated pre-chamber combustion system for otherwise standard spark ignition engines found in current passenger vehicles. This next generation prechamber design simply replaces the spark plug in a conventional spark ignition engine. Turbulent Jet Ignition enables very fast burn rates due to the ignition system producing multiple, widely distributed ignition sites, which consume the main charge rapidly. This high energy ignition results from the partially combusted (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Data of a 2011 Chevrolet HHR vehicle [41] are shown together with the parameters used for the range policies (2)- (5).…”
Section: Appendix 1 Parameters Used In This Papermentioning
confidence: 99%
“…Data of a 2011 Chevrolet HHR vehicle [41] are shown together with the parameters used for the range policies (2)- (5).…”
Section: Appendix 1 Parameters Used In This Papermentioning
confidence: 99%
“…Fuel economy benefits of over 16% over a US EPA City Driving Cycle with HCCI implementation on a baseline 2.3 l direct-injection (DI) engine with twin-independent variable valve timing (VVT) and exhaust gas recirculation (EGR) have been demonstrated.75 Several other studies have provided insight into the fuel economy benefits of implementing HCCI technology. 74,[76][77][78][79][80] Controlled autoignition (CAI) is another promising combustion technology that allows the full potential of HCCI to be harnessed but with fewer risks in terms of pre-ignition and engine knock. [80][81][82][83] It is worth noting that HCCI, CAI and lowtemperature combustion (LTC) modes at large lead to reduced exhaust gas temperatures, hence reducing the availability of the exhaust gas energy.…”
Section: Managing the Engine's Energy Dissipationmentioning
confidence: 99%
“…Due to the significant knock mitigation and the ability to ignite highly diluted mixtures, pre-chamber ignition is recently reconsidered for its application in highly efficient automotive SI engines. [114][115][116] The pre-chamber ignition system can be classified into passive and active systems; comprehensive reviews regarding the pre-chamber ignition technologies can be found in Toulson and Alvarez's work. 117,118 The passive pre-chamber spark plug exchanges the gas depending on the pressure difference between the ports of the orifice channels and the inner aerodynamics of the pre-chamber.…”
Section: Pre-chamber Ignitionmentioning
confidence: 99%